MODERNISASI PENDIDIKAN ISLAM INDONESIA: PENGALAMAN MUHAMMADIYAH - Faizal Lubis; Muhammad Rusdi (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
The modernization of Islamic education in Indonesia is a historical process that cannot be separated from the role of modernist Islamic organizations, one of which is Muhammadiyah. Since the early 20th century, Muhammadiyah has emerged as a pioneer in the renewal of Islamic education through the integration of Islamic values ​​with the modern education system. This article aims to analyze Muhammadiyah's concepts, practices, and contributions to the modernization of Islamic education in Indonesia, particularly in terms of educational objectives, curriculum, learning methods, human resources, and educational institutions. This research uses a qualitative approach with library research on various relevant primary and secondary sources, such as books, journal articles, Muhammadiyah organizational documents, and official reports. The results indicate that Muhammadiyah's modernization of Islamic education is rooted in the spirit of tajdid (renewal) initiated by K.H. Ahmad Dahlan, which rejects the dichotomy between religious knowledge and general knowledge. Muhammadiyah develops an integral education that balances spiritual, intellectual, and social dimensions. Furthermore, Muhammadiyah plays a significant role in expanding access to education even to remote areas and building an education system oriented towards the advancement of the people and the nation. This finding confirms that the modernization of Muhammadiyah Islamic education is not only adaptive to the development of the times, but also contributes to forming the character of national education which is characterized by progressive Islam.